The Role of Aspartate Aminotransferase to Platelet Ratio Index as a Non-Invasive Predictor of Variceal Etiology of Upper Gastrointestinal Bleeding - Shrestha, Ashish; Sharma, Pasanda; Lama, Anjila; Gurung, Ram Bahadur (Journal of Lumbini Medical College, 2020)
Introduction: Non-invasive strategies to predict variceal from non-variceal bleeding will be highly beneficial for pre-emptive management of Upper Gastrointestinal Bleeding (UGIB). This study aimed to assess the role of aspartate aminotransferase (AST) to platelet ratio index (APRI) as a non-invasive predictor of variceal etiology of UGIB. Methods: This was a retrospective descriptive study conducted at Endoscopy Department of Dhulikhel Hospital between January 2017 and December 2019 in patients presenting with acute UGIB. We assessed the diagnostic utility of the APRI score relative to other objective measures by Area Under the Receiver Operating Characteristic (AUROC) curve analysis. Results: A total of 158 patients with history of UGIB were included in the study. There were total 123 males (77.8%) and the mean age of the patients was 50.3±16.1 years. The APRI score performed well in predicting a variceal etiology of acute UGIB, with AUROC 0.9. When APRI was used at cut-off of 1.3, it had a sensitivity of 84.1% and specificity of 76.8%, a positive predictive value of 70.7% and a negative predictive value of 89.9% while predicting variceal etiology of UGIB at presentation. The relative risk of varices at an APRI cut-off of 1.3 is 17.5 with a p-value of <0.0001. Conclusion: The present study highlighted that APRI score can be used as an objective metric that helps to predict a variceal etiology of acute UGIB.